PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BAGI SISWA KELAS IV SEKOLAH DASAR - Rizky Nugroho (Universitas Kanjuruhan Malang, 2018)
This research aims to produce learning materials using the Contextual Teaching and Learning approach (CTL) that is valid, practical, and effective for fourth grade of elementary school. This research is a development study using 4-D development model which includes four stages of define, design, develop and disseminate. The result of the research shows that learning materials is valid with very good category by validator. Implementation of learning materials can be done with very good category and students responses to learning materials is in very good category. There are differences in learning motivation and significant learning result between experimental classes using learning materials using the Contextual Teaching and Learning approaches and control classes that do not use learning materials result of development. Based on the results of the study, it can be concluded that the development of learning materials using the Contextual Teaching and Learning approach fulfills the valid, practical, and effective criteria.